U-Turn Analysis on Accident Risk Levels on Kaligangsa Road, Tegal City: Evaluasi Risiko Kecelakaan pada U-Turn: Studi Kasus Jalan Raya Kaligangsa, Kota Tegal - Hilmy Dwi Saputra; Icha Berliana Navyano; Muhammad Ziddan Rezka; Bambang Istiyanto (Universitas Negeri Surabaya, 2025)
This study analyzes the impact of U-turns on potential traffic accidents along Kaligangsa Highway, Tegal City, using the Traffic Conflict Technique (TCT) method. Although U-turns play a crucial role in road geometric planning, they often become critical points that may lead to accidents due to sudden vehicle maneuvers. The TCT method is applied to assess potential traffic conflicts based on vehicle speed, distance between vehicles, and road user interactions. Direct observations were conducted at several U-turn locations along the road. The analysis results indicate that the presence of U-turns significantly contributes to an increased risk of accidents, particularly during peak hours and at locations with suboptimal geometric design. Non-standard U-turn designs, unclear traffic signage, and undisciplined driver behavior further escalate the risk of traffic conflicts. Therefore, this study recommends improvements in U-turn design, enhanced traffic monitoring, and driver education to improve road safety..